2013
DOI: 10.1007/s00384-013-1678-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adenovirus-mediated PTEN gene on ulcerative colitis-associated colorectal cancer

Abstract: PTEN plays an important role in the inflammation-dysplasia-carcinoma sequence and may be a new molecular target in preventing and treating ulcerative colitis-associated colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…PTEN promotes apoptosis (17), which contributes to the aggregation of UC (18). The present study observed the upregulation of PTEN in UC, and that it had an enhancing effect on the apoptosis of HCnEpCs induced by LPS.…”
Section: Discussionsupporting
confidence: 60%
“…PTEN promotes apoptosis (17), which contributes to the aggregation of UC (18). The present study observed the upregulation of PTEN in UC, and that it had an enhancing effect on the apoptosis of HCnEpCs induced by LPS.…”
Section: Discussionsupporting
confidence: 60%
“…By contrast, the tumor suppressor phosphatase and tensin homology deleted on chromosome 10 (PTEN) inhibits the actions of PI3K 38 . Because Akt signaling is important in CAC 39 , we assessed Akt activation in Aim2 −/− mice. Similar expression of total Akt (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3). Previous studies have shown that transduction of the wild-type PTEN gene into cancer cells induces apoptosis (25,26). Here, we observed that PTEN-VP22 enhanced apoptosis relative to PTEN alone, whereas VP22 had no effect on apoptosis levels (Fig.…”
Section: Discussionmentioning
confidence: 49%